Clinical Features and Treatment Outcomes among Children with Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis: A 20-Year Study in a Tertiary Referral Hospital - Susheera Chatproedprai; Vanvara Wutticharoenwong; Therdpong Tempark; Siriwan Wananukul (Dermatology Research and Practice)
Aim. To determine the probable causative factors, clinical features, and treatment outcomes of Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and SJS-TEN overlap in children. Methods. A 20-year database review of all children diagnosed with SJS/TEN/SJS-TEN overlap at the King Chulalongkorn Memorial Hospital, Thailand. Results. 36 patients (M : F, 16 : 20) with the mean age of 9.2±4.0 years were identified. There were 20 cases of SJS, 4 cases of SJS-TEN overlap, and 12 cases of TEN. Drugs were the leading cause for the diseases (72.3%); antiepileptics were the most common culprits (36.1%). Cutaneous morphology at presentation was morbilliform rash (83.3%), blister (38.9%), targetoid lesions (25.0%), and purpuric macules (2.8%). Oral mucosa (97.2%) and eye (83.3%) were the 2 most common mucosal involvements. Majority of the cases (77.8%) were treated with systemic corticosteroids, intravenous immunoglobulin, or both. Treatment outcomes between those who received systemic therapy and those who received only supportive care were comparable. Skin and eye were the principal sites of short-term and long-term complications. Conclusions. SJS/TEN are not common but are serious diseases which lead to significant morbidities in children. Early withdrawal of suspicious causes and meticulous supportive care are very important. This study found that the systemic therapy was not superior to supportive care because the treatment outcomes for both groups were comparable.